Hydrogen production via dehydrogenation of alcohols using ruthenium hexamethylenetetramine complex - Preeti Devi; Senthilkumar Muthaiah (Academia Green Energy)
Being a zero-carbon source, the hydrogen economy is considered to be better than the fuel economy as it produces only water vapor even after complete combustion. Still, it suffers from two major drawbacks, namely (1) the production of green hydrogen from sustainable resources and (2) the storage and transportation of hydrogen. The use of liquid organic hydrogen carriers (LOHCs) such as alcohols, amines, etc. has been found to be a better and more secure way to store and transport hydrogen. Catalytic hydrogenation and dehydrogenation of LOHCs using transition metal complexes are known as the best methods to load and unload hydrogen for storage and transportation. Here, in this article, we show the amount of hydrogen produced during the catalytic dehydrogenation of LOHCs like alcohols using a very simple and cheap gas burette method. The dehydrogenative oxidation of alcohols was done using a well-defined [Ru(p-cym)HMTA]Cl2 complex with a catalyst loading of 0.5 mol%. Hydrogen estimation was done for different alcohol substrates. A comparison was made between theoretical and experimental yields of the released hydrogen.